Site of desire 1998 - Taipei Biennial. - Taipei Biennial 1998; Chang, Fangwei; Chen, Yuhsun; Hsiao, H.H. Michael; Kang, Sangjung; Kim, Sunhee; Miki, Akiko; Munlee, Lin; Nanjo, Fumio; Yanai, Hiroyuki (Tapei : Taipei Fine Arts Museum, 1998)
Beom, Kim ; Bocsu, Jung ; Boutique, Ad ; Cai Guo-Qiang ; Chen Zhen ; Chiehjen, Chen ; Chinho, Huang ; Chumming, Hou ; Daisuke, Nakayama ; DeanE, Mei ; Gu Dexin ; Fuyu, Chien ; Goangming, Yuan ; Hairu, Tsai ; HsuehO, Wei ; Hyoungkuhn, Oh ; Jeonghwa, Choi ; Junichi, Kusaka ; Junjieh, Wang ; Miwa, Yanagi ; Mo, Bahc ; Nobuyoshi, Araki ; Qingsong, Wang ; Shihfen, Liu ; Sora, Kim ; Suknam, Yun ; Tan, Xu ; Tatsuo, Miyajima ; Tienchang, Wu ; Tsuyoshi, Ozawa ; Wu Ma-Li ; Xu Bing ; Yayoi, Kusama ; Yilin, Lin ; Yoshihiro, Suda ; Yukinori, Yanagi ; Zheng Guogu
biografie
Site of desire 1998 - Taipei Biennial, organized by Taipei City Government, Taipei Fine Arts Museum, Taipei, June 13 - September 6, 1998
Engels & Chinees
kunstcatalogus